Pengabdian di Desa Samangki: Kiprah Mahasiswa dalam Mewujudkan Perubahan: Service in Samangki Village: Student Action in Bringing Change to Life - Wahyuni Nur, Sri Reski; Maryam, Maryam (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The aim of this activity is to provide understanding and training about religious teachings and practices so that people are more aware and understand about people's beliefs. There are several methods of community service in the form of education and teaching, social activities and spreading kindness, religious activities and friendship. The results of the programs implemented made the local community aware of differences in opinion and accustomed to the separation of men and women in several activities.